Contrast Sensitivity Function and Low Vision - Woo, George C (Canadian Journal of Optometry, 1982)
The Canadian Association of Optometrists through its educational endowment fund recently provided the funds for a custom designed contrast sensitivity function unit at the low vision clinic of the University of Waterloo. Its purpose is to enhance the capability of low vision clinicians to evaluate residual functional vision of some low vision patients where conventional visual acuity approaches fail to quantify any functional loss of vision.